A Peer-Led HIV Medication Adherence Intervention Targeting Adults Linked to Medical Care but without a Suppressed Viral Load. (September 2015) - Enriquez, Maithe; Cheng, An-Lin; Banderas, Julie; Farnan, Rose; Chertoff, Keyna; Hayes, Deana; Ortego, Gerry; Moreno, Jose; Peterson, Jane; McKinsey, David
Background: Non-adherence to antiretroviral (ART) treatment remains a prevalent problem even among the segment of the U.S. HIV population that is 'linked' to medical care. Methods: Controlled pilot feasibility study with ART experienced adult patients (n = 20) linked to HIV medical care without suppressed viral load. Patients were randomized to a peer-led HIV medication adherence intervention named `Ready' or a time equivalent `healthy eating' control arm. Lay individuals living with HIV were trained to facilitate `Ready'. Results: Patients had been prescribed a mean of three prior ART regimens. The group randomized to `Ready' had significantly improved adherence. MEMS and pharmacy refill data correlated with viral load log drop. Higher readiness for healthful behavior change correlated with viral load drop and approached significance. Conclusion: A peer-led medication adherence intervention had a positive impact among adults who had experienced repeated non-adherence to HIV treatment. A larger study is needed to examine intervention dissemination and efficacy.